Arctic cooperation after Russia's break with the West. Issue 5 (28th May 2022) - Unknown
Abstract : Multilateral relations over the Arctic, in which Russia has played a significant role given its large Arctic coast, have been largely frozen since the invasion of Ukraine in February 2022. This includes cooperation over scientific issues, which will lead to a loss of Western access to data and knowledge about the region with damaging consequences for global climate research. The mutually beneficial legal agreements and instruments that have underwritten past Arctic cooperation are not at risk, however. Russia may take steps to further militarise some of its Arctic-adjacent regions in response to the poor performance of its conventional forces in Ukraine and the fact that Finland and Sweden are on track to join NATO.